Precolonial coastal archaeology between Table Bay and Yzerfontein, Western Cape, South Africa: a review of historical and recent observations - Orton, Jayson; Avery, Graham; Halkett, David; Hart, Tim; Kaplan, Jonathan (Southern African Humanities, 2020)
This paper reviews the precolonial coastal archaeological record from Table Bay to Yzerfontein. The observations include amateur and professional historical reports, academic publications and a large body of grey literature generated by cultural resources management practitioners. Primary archaeological information is relatively sparse due to the extensive historical development of the coastline, with most data generated by recent CRM work. The radiocarbon record established from burials and shell middens extends back through 6000 years; beyond that isolated occurrences of Middle and Earlier Stone Age materials exist, notably including the Middle Stone Age shell midden, Ysterfontein 1. Further archaeological sites are likely to occur in the review area but sites in better context are more likely to be found in the north where development pressure has been less intense. Solutions need to be found to ensure the reporting and rescue of accidental finds made during construction work so as to prevent the ongoing loss of archaeological information and burials. Heritage policing is virtually non-existent and fines for heritage contraventions are too small to act as suitable incentives. Given the continuing development around Table Bay, CRM work will continue to drive the generation of archaeological data in the area. KEY WORDS: Table Bay, Bloubergstrand, Melkbosstrand, Yzerfontein, cultural resource management, shell middens, shell scatters, human burials.